Governance Planning in Tourism Management in Yogyakarta City - Irfan, Muhammad; Purnama, Gilang (Prodi Administrasi Publik FISIP UNPAS, 2025)
This study aims to determine Governance in Tourism Planning towards World Tourism in Bappeda of Yogyakarta City. This study uses a descriptive research method with a qualitative approach. Where the type of data consists of primary data obtained through interviews, observations and direct documentation in the field, while secondary data is obtained from data that has been collected by researchers through documents related to the study. The analysis techniques in this study are data reduction (Data Reduction), data presentation (Data Display), and conclusion drawing (Conclusion Drawing).The results of the study indicate that the Governance process in Tourism Planning towards World Tourism in Bappeda of Yogyakarta City has been running since Pangandaran began to separate from Ciamis. Based on the results of the study, it can be concluded that the Collaborative Governance process in Tourism Planning in Yogyakarta City has been organized and also invites the community to contribute to the development of tourism in Yogyakarta City.